Book Review: Manga in Libraries: A Guide for Teen Librarians - Sara Lowe (Journal of Anime and Manga Studies)
Manga, comics or graphic novels originating from Japan, are popular both inside and outside of Japan. Sales of manga have quadrupled since 2020. In 2023, almost 49% of graphic novels sold were manga. This increased popularity means manga is well represented in library purchases. In 2023, according to a School Library Journal survey, manga comprised 43 percent of high school graphic novel purchases and 64 percent of respondents noted that, in their library, manga was the most popular graphic novel with teenagers. With the popularity of manga, and the rise in the amount of manga libraries purchase, Manga in Libraries’ purpose is to fill a professional development gap in public libraries. It succeeds in its purpose.